2020
DOI: 10.1136/bjophthalmol-2020-316401
|View full text |Cite
|
Sign up to set email alerts
|

Optimised retinopathy of prematurity screening guideline in China based on a 5-year cohort study

Abstract: PurposesTo develop an optimised retinopathy of prematurity (ROP) screening guideline by adjusting the screening schedule and thresholds of gestational age (GA) and birth weight (BW).MethodsA multicentre retrospective cohort study was conducted based on data from four tertiary neonatal intensive care units in Shanghai, China. The medical records of enrolled infants, born from 2012 to 2016 who underwent ROP examinations, were collected and analysed. The incidence and risk factors for ROP were analysed in all inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…7,11) Advanced training for neonatologists, ophthalmologists, and neonatal nurses is often lacking, oxygen saturation is not monitored, and ROP is seen in the smallest infants if they do survive as well as in more mature preterm infants. 12) These regions include middle-income regions of Latin America, East and South Asia, Eastern Europe, and Central Asia according to Blencowe et al 2) During this third epidemic, the mean BWs of ROP babies needing treatment ranged from 737 to 763 g (range, 440-1785 g) in the UK, Canada, and the USA, while mean gestational age (GA) ranged from 25.3 to 25.6 weeks (range, [22][23][24][25][26][27][28][29][30][31][32]. 12) Meanwhile, babies affected in low-and middle-income countries have a far wider range of BWs and GAs.…”
Section: Three Phases Of Rop "Epidemics"mentioning
confidence: 99%
See 1 more Smart Citation
“…7,11) Advanced training for neonatologists, ophthalmologists, and neonatal nurses is often lacking, oxygen saturation is not monitored, and ROP is seen in the smallest infants if they do survive as well as in more mature preterm infants. 12) These regions include middle-income regions of Latin America, East and South Asia, Eastern Europe, and Central Asia according to Blencowe et al 2) During this third epidemic, the mean BWs of ROP babies needing treatment ranged from 737 to 763 g (range, 440-1785 g) in the UK, Canada, and the USA, while mean gestational age (GA) ranged from 25.3 to 25.6 weeks (range, [22][23][24][25][26][27][28][29][30][31][32]. 12) Meanwhile, babies affected in low-and middle-income countries have a far wider range of BWs and GAs.…”
Section: Three Phases Of Rop "Epidemics"mentioning
confidence: 99%
“…A multicenter study conducted in Shanghai in 2012-2016 showed an ROP incidence of 15.9% (892/5,606) among all infants undergoing ROP screening. 31) In Southwest China, 12.8% (206/1,614) of premature infants with a GA < 37 weeks…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…The incidence of ROP in Shanghai was 17.8%, and the treatment rate was 6.8% in 2013 [ 13 ]. A recent study reported that the incidence of ROP in Shanghai was 15.9%, and the treatment rate was 1.1% in 2021 [ 14 ]. Tianjin Eye Hospital is the only medical institutions to carried out the ROP screening in Tianjin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous reports on the risk factors of ROP (10,(22)(23)(24), little is known about the factors affecting its spontaneous regression. Only two small-scale studies have identified the factors influencing ROP regression.…”
Section: Discussionmentioning
confidence: 99%